Randomized, double‐blind, placebo‐controlled phase 1 study to evaluate the safety and pharmacokinetics of high doses of ubiquinol in healthy adults. Issue 1 (7th December 2021) - Mitsui, Jun; Matsukawa, Takashi; Tanaka, Masaki; Saito‐Sato, Naoko; Nakamoto, Fumiko Kusunoki; Yasuda, Tsutomu; Naruse, Hiroya; Matsukawa, Miho Kawabe; Ishiura, Hiroyuki; Nagase, Midori; Yamamoto, Yorihiro; Kuzuyama, Haruko; et al.
Abstract: Background: Multiple system atrophy (MSA) is an intractable neurodegenerative disease. Higher frequencies of carriers of the V393A variant in COQ2 and lower levels of coenzyme Q10 (CoQ10) in body tissues have been reported in patients with MSA than in healthy controls. On the basis of the hypothesis that CoQ10 supplementation may slow the progression of MSA, we have been developing CoQ10 as an investigational drug for MSA. Methods: A single‐center, randomized, double‐blind, placebo‐controlled phase 1 study of ubiquinol in healthy adult male volunteers was conducted. Participants were randomly assigned to groups that orally receive 900, 1200, and 1500 mg of ubiquinol or placebo daily for 14 days. Safety was assessed by examining the frequency and severity of adverse events. The levels of ubiquinol in plasma and total CoQ10 in peripheral blood mononuclear cells and cerebrospinal fluid were investigated. Results: Thirty‐two participants provided informed consent to participate in this study. No clinically relevant changes in standard laboratory tests, physical examination, vital signs, or electrocardiogram attributable to ubiquinol administration were observed in any groups. The trough of plasma ubiquinol levels after repeated administration for 14 days reached a steady state, and the plasma ubiquinol levels in the 1500 mg/day‐administered group tended to be the highest. Conclusions: High‐dose ubiquinol supplementation was shown to be safe and tolerated when administered orally to healthy adult males at a maximum dosage of 1500 mg/day for 14 days (UMIN Clinical Trials Registry number, UMIN000016695).